A virus-free vector for the transfection of somatic cells to obtain IPSC - Varli, Hanife Sevgi; Alkan, Funda; Demirbilek, Murat; Turkoglu, Nelisa (SPRINGER, 2019)
Reprogramming of somatic cells to induced pluripotent stem cells (iPSCs) is a promising tool for regenerative medicine. The fibroblast cells are the most commonly used cell type for this purpose thanks to their easy accessibility. In this study, we used the fibroblast cell line to introduce the main transcription factors (Oct4, Klf4, Sox2) for reprogramming. Controversy to literature, we used a virus-free method for introduction OKS. We developed an octadecylamine-based cationic lipid nanoparticle as a nonviral carrier. The cationic nanoparticle was prepared via the emulsion-solvent evaporation method. We used the formulation OLN32 with 29.7 +/- 3.16 mV zeta potential and 118.3 +/- 3.05 nm size for introducing OKS. The fibroblast L929 cell line was transfected with OLN-OKS conjugates, and the transfection efficiency was followed by observing GFP expression. The transfection efficiency was found at 72%. The expression of OKS was detected by RT-qPCR and the transfection factors were determined to be amplified after the 11th cycle.
Keywords: IPSC; Reprogramming; Non-viral; Nanoparticle; Octadecylamine; Fibroblast; PLURIPOTENT STEM-CELLS; GENE DELIVERY; IN-VITRO; NONVIRAL VECTORS; NANOPARTICLES; GENERATION; INTEGRATION; Chemistry; Science & Technology - Other Topics; Materials Science